ROLE OF CAMEL MILK IN THE MANAGEMENT OF DIABETES MELLITUS (MADHUMEHA) W.S.R. OF TYPE 1 DIABETES: REVIEW ARTICLE - Gupta Payal; Mishra Pramod Kumar; Sharma Indumati (International Journal of Applied Ayurved Research, 2017)
Diabetes mellitus (DM) is a disease characterized by a high level of blood sugar (i.e., glucose) that results from the failure of the body to produce sufficient insulin (type 1 diabetes). In Ayurved, it can be correlated with “Madhumeha”.”Madhumeha” caused by vitiation of vata dosha .In a country with the hightest incidence of diabetes in the world, a potential preventative treatment has been found in an unlikely place: camels.Ayurveda has referred medicinal value of camel milk under the classification of “Dugdha varga”(Milk classification ).camel milk has a high vitamin and mineral content and immunoglobulin content. Camel milk contains high concentration of insulin i.e. 52 U/L to 59 U/L. The efficacy of camel milk consumption as an adjunct to routine diabetic management in maintaining long-term glycaemia control in type I diabetes was assessed during a 52 week randomized study. Throughout the duration of study, 12 randomly assigned patients underwent routine diabetic management(diet ,exercise ,parental insulin supplementation) and 12 randomly assigned patients additionally undertook daily consumption of raw camel milk (500ml/day).. In addition to that, one patient of the group is completely cured from DM after 8 months of consumption of camel milk, and gets rid of using insulin totally. In the contrary, there was no significant change in c-peptide or anti- insulin antibodies. This study demonstrated that, camel milk, as an adjunct to insulin therapy, was safe and efficacious in improving long-term glycaemic control, and helps in the reduction of insulin requirement in type 1 diabetic patients.